Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1016/s1734-1140(12)70743-0
|View full text |Cite
|
Sign up to set email alerts
|

Hematological effects of exposure to mixtures of selected ethylene glycol alkyl ethers in rats

Abstract: Exposure to various ethylene glycol monoalkyl ethers (EGAEs) is known to result in hemolytic effect caused by their metabolites, appropriate alkoxyacetic acids, generated via both alcohol dehydrogenase and aldehyde dehydrogenase. It has been shown in many studies that administration of single doses of EGAEs to rats lead to dose- and time-dependent hemolytic anemia. The repeated exposure to isopropoxyethanol (IPE), and butoxyethanol (BE), contrary to methoxyethanol (ME) and ethoxyethanol (EE), resulted in signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Following testicular exposures, EGEs are activated in affected cells by the action of alcohol dehydrogenase (ADH) and aldehyde dehydrogenase (ALDH) respectively [ 18 ]. Methoxyacetic acid (MAA), a metabolite of EGME is responsible for the teratogenicity, hematotoxicity, gonadotoxicity, immunotoxicity, and embryotoxicity of EGME [ 5 , [19] , [20] , [21] ]. Severe effects of EGEs on sperm and testes as a whole have been documented in humans [ 5 ], but have not been fully investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Following testicular exposures, EGEs are activated in affected cells by the action of alcohol dehydrogenase (ADH) and aldehyde dehydrogenase (ALDH) respectively [ 18 ]. Methoxyacetic acid (MAA), a metabolite of EGME is responsible for the teratogenicity, hematotoxicity, gonadotoxicity, immunotoxicity, and embryotoxicity of EGME [ 5 , [19] , [20] , [21] ]. Severe effects of EGEs on sperm and testes as a whole have been documented in humans [ 5 ], but have not been fully investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Hematological indices including HGB and HCT are influenced by various factors. Several studies indicated that pulsed electric field exposure [ 14 ], herbal extracts [ [15] , [16] ], and chemicals [ 17 ] can influence hematological parameters, but in this study, alteration ranges were minimal and within the normal range, thus it is difficult to judge directly by test substance [ 18 ]. Generally, increased RDW indicates the presence of cell of different sized and related with iron deficiency anemia if accompanied by a decrease of MCV.…”
Section: Discussionmentioning
confidence: 96%
“…For example, ME attenuated hematotoxic action of isopropoxyethanol (IPE) in rats at the beginning of the exposure increased its harmful effects at the end of the treatment [18]. Aliphatic alcohols, i.e., ethanol, n-propanol, and n-butanol, almost completely inhibited the hemolytic effect of BE in rats, and significantly reduced the urinary excretion of butoxyacetic acid (BAA), a metabolite of BE.…”
Section: Discussionmentioning
confidence: 99%
“…Control rats (1 group) were given the equivalent volume of saline. The applied doses and route of administration were chosen based on the previous work output [18].…”
Section: Animal Treatmentmentioning
confidence: 99%
See 1 more Smart Citation